Transcriptional Modulation of Polyamine Metabolism in Fruit Species Under Abiotic and Biotic Stress - Fortes, Ana Margarida; Agudelo-Romero, Patricia; Pimentel, Diana; Alkan, Noam (Frontiers in Plant Science, 2019)
Polyamines are growth regulators that have been widely implicated in abiotic and biotic stresses. They are also associated with fruit set, ripening and regulation of fruit quality-related traits. Modulation of their content confers fruit resilience, with polyamine application generally inhibiting postharvest decay. Changes in the content of free and conjugated polyamines in response to stress are highly dependent on the type of abiotic stress applied or the lifestyle of the pathogen. Recent studies suggest that exogenous application of polyamines or modulation of polyamine content by gene editing can confer tolerance to multiple abiotic and biotic stresses simultaneously. In this review, we explore data on polyamine synthesis and catabolism in fruit related to pre- and postharvest stresses. Studies of mutant plants, priming of stress responses, and treatments with polyamines and polyamine inhibitors indicate that these growth regulators can be manipulated to increase fruit productivity with reduced use of pesticides and therefore, under more sustainable conditions.